Encephalitis Caused by Pathogens Transmitted through Organ Transplants, United States, 2002–2013 - Basavaraju, Sridhar V. (Centers for Disease Control and Prevention, 2014)
The cause of encephalitis among solid organ transplant recipients may be multifactorial; the disease can result from infectious or noninfectious etiologies. During 2002–2013, the US Centers for Disease Control and Prevention investigated several encephalitis clusters among transplant recipients. Cases were caused by infections from transplant-transmitted pathogens: West Nile virus, rabies virus, lymphocytic choriomeningitis virus, and Balamuthia mandrillaris amebae. In many of the clusters, identification of the cause was complicated by delayed diagnosis due to the rarity of the disease, geographic distance separating transplant recipients, and lack of prompt recognition and reporting systems. Establishment of surveillance systems to detect illness among organ recipients, including communication among transplant center physicians, organ procurement organizations, and public health authorities, may enable the rapid discovery and investigation of infectious encephalitis clusters. These transplant-transmitted pathogen clusters highlight the need for greater awareness among clinicians, pathologists, and public health workers, of emerging infectious agents causing encephalitis among organ recipients.